Compliance, integrity, and prevention in the corporate sector: the collective mindsets of compliance officers in the USA - Pohlmann, Markus; Starystach, Sebastian (Organizational crime, 2023)
The paper reconstructs which function senior compliance professionals of multinational companies based in the US attribute conceptually to compliance. Furthermore, the paper critically examines the subsequent consequences of these collectively shared concepts for the prevention, identification, and prosecution of rule violations within and by companies. The database consists of problem-centered interviews conducted in Germany and the USA with high-ranking compliance employees of multinational companies (n = 27). The paper addresses in particular the findings for the compliance officers (n = 12) from the US. Our study opens the black box of the theories-in-use concerning compliance as well as prevention, and discusses what kind of sensemaking is established in the compliance departments of big US firms. By using the qualitative method of collective mindset analysis, it is answering the question as to whether integrity and prevention has to be understood as a stronghold of a rational business strategy or merely as a mandatory form of window dressing for the protection of the company. Our findings are that the theories-in-use are very much dominated by a rational-choice perspective of the firm as corporate actor, in which communication, education, and monitoring is focused on the employees, adjusting their deliberative action, and helping them to avoid wrongdoings. One side effect of this rational-choice perspective on organizational wrongdoings is that compliance professionals can label rule violations as the result of decisions attributable to individuals and not as the result of organizational structures. By these means, compliance serves the purpose of avoiding criminal prosecution of the company, especially the application of corporate criminal law.